Gonadal maturation, fecundity and hatching performance of wild caught tiger shrimp Penaeus monodon using unilateral eyestalk ablation in captivity (Journal of the Bangladesh Agricultural University, 2016)
In this study, the effects of eyestalk ablation on maturation, moulting, spawning and hatching rate of wild caught Penaeus monodon were investigated. Twenty males (M) and 30 eyestalkablated and 30 nonablated females (F), all individually marked (M: F=1:3) were stocked into two 15ton capacity (each) maturation tank. All the ablated females moulted in 7.92±0.24 (mean±standard error) days, and first spawning occurred 3.2±0.20 days following eyestalk ablation. While twenty-five ablated females spawned, producing an average of 296,160±26,589 eggs, only eight nonablated females spawned, producing an average of 195,462±20,565 eggs during the investigation period of 120 days. A significant positive correlation between fecundity and female body weight (P